Internet Marketing Produk Crochet Sebagai Peluang Usaha Rumahan Bagi Ibu-Ibu Dawis - Septi Fajarwati (IKIP PGRI Bojonegoro, 2021)
ABSTRACT75% of dawis members in Bantarwuni village RT 03 RW 03 Kembaran District are housewives who have no income. The desire to have their own income to improve the family's economy needs special attention. With capital from knitting skills using crochet techniques that they already have, they need support so that it can become a profitable home business opportunity. Given the limited knowledge in marketing crochet products, the purpose of this service is to provide internet marketing training so that crochet products can be known more widely. The implementation of this service activity began with coordination between service implementers and partners, followed by the implementation of training and finally an evaluation of service activities. The training process was carried out by providing knowledge about internet marketing and direct practice on how to take advantage of the WA business feature, how to create Facebook, Instagram and Shopee accounts and practicing how to take pictures or photos of attractive products as promotional material. This service activity invited all Dawis members so that each of the Dawis members has good internet marketing knowledge. It is hoped that the desire to have their own income can be realized. Keywords: dawis, internet marketing, crochet. ABSTRAKAda sebanyak 75% anggota dawis di desa Bantarwuni RT 03 RW 03 Kecamatan Kembaran adalah ibu rumah tangga yang tidak berpenghasilan. Keinginan untuk mempunyai penghasilan sendiri untuk meningkatkan perekonomian keluarga perlu mendapatkan perhatian khusus. Bermodal dari ketrampilan merajut menggunakan teknik crochet yang telah dimiliki, perlu mendapat dukungan agar dapat menjadi peluang usaha rumahan yang menghasilkan. Mengingat keterbatasan pengetahuan dalam memasarkan produk crochet, maka tujuan diadakan pengabdian ini adalah memberikan pelatihan internet marketing agar produk crochet dapat dikenal lebih luas. Pelaksanaan kegiatan pengabdian ini akan dimulai dengan koordinasi antara pelaksana pengabdian dengan mitra, dilanjutkan dengan pelaksanaan pelatihan dan terakhir dilakukan evaluasi kegiatan pengabdian. Proses pelatihan dilakukan dengan memberikan pengetahuan tentang internet marketing dan praktek secara langsung cara memanfaatkan fitur WA bisnis, membuat akun Facebook, Instagram dan Shopee serta praktek cara mengambil gambar atau foto produk yang menarik sebagai bahan promosi. Kegiatan pengabdian ini melibatkan seluruh anggota dawis sehingga masing-masing dari ibu-ibu dawis memiliki pengetahuan internet marketing dengan baik, diharapkan keinginan mempunyai penghasilan sendiri dapat terwujud.Kata kunci : dawis, internet marketing, crochet